Consolidation in a wildlife tourism industry: the changing impact of whale shark tourist expenditure in the Ningaloo Coast region - Catlin, James; Jones, Tod; Norman, B.; Wood, David (McGraw-Hill, 2010)
In this paper, we examine the expenditure of whale shark tour participants at Ningaloo Marine Park, Western Australia; the location of the world's first whale shark tourism industry, established in 1989. We demonstrate that in 2006, participants' expenditure in the region was $894 per trip, total expenditure was $6.0 million (all figures are in Australian dollars), and between $2.4 and $4.6 million would have been lost to the region if whale shark tourism did not exist. Our measure of participants' expenditure is substantially lower than the calculation of $2370 per participant from a previous study of whale shark tourists using data collected in 1995. We argue that this is consistent with a change in the types of wildlife tourists that participate in an activity as the industry reaches the point of consolidation. Our results also suggest that using old data to forecast wildlife tourists' expenditure needs to take into account the industry's stage of development.